Concentration of fallout Cesium-137 in soils of the Rio de Janeiro State, Brazil - Fernando C. A. Ribeiro; Dejanira da Costa Lauria; José Ivan Rodrigues Silva; Erica Souto Abreu Lima; Nelson Moura Brasil do Amaral Sobrinho; Daniel Vidal Perez (Brazilian Journal of Radiation Sciences)
The distribution of fallout 137Cs in soil samples of the Rio de Janeiro State was investigated. Two-hundred sixty-two samples of soil were analyzed for 137Cs by gamma spectrometry. A reference data set was built containing thirty-six detected values (14%) and two hundred twenty-six (86%) multiple detection limits of non-detected observations. Distribution pattern of the radionuclide, as well their controlling factors were evaluated based on statistical methods for censored data set (with non-detected observations). The mean of concentration values of thirty-six detected observations was 1.25 Bq.kg-1, while for the censored data sets the mean value was 0.51 Bq.kg-1. The references values for the Rio de Janeiro State were estimated as 1.44 Bq.kg-1 (75th) and 1.78 Bq.kg-1 (90Th) (considering the year of 2015). 137Cs concentrations tend to be higher in soils with high levels of organic matter and clay and locations with high levels of these parameters would provide higher Cs fixation. No influence of the rainfall index and soil pH on the Cs content in soil was observed. The data and information gathered in this study provide valuable information for decision making purposes in case of soil contamination.